The Trump tapes : Bob Woodward's twenty interviews with President Donald Trump [compact disc, unabridged] - Woodward, Bob, 1943- (Audio Works, Simon & Schuster Audio, 2022)
The intimate and astonishing audio archive of Bob Woodward's 20 interviews with Donald Trump. In this up-close, unvarnished self-portrait of Trump and his presidency, listeners will hear Trump as Woodward did: profane, incautious, divisive, and deceptive, but also engaging and entertaining, ever the host and the salesman, trying to sell his presidency to win Woodward over. Relying on familiar devices, airing grievances, stoking divisions, repeating himself to a staggering degree, as if saying something often and loud enough will make something true, Trump uses his voice as a concussive instrument, pounding in the listener's ear. Woodward at times breaks frame from the interviews to provide essential context or clarification. But for the most part the interviews proceed uninterrupted, fulfilling Woodward's goal of presenting Trump's voice and words for the historical record, and offering listeners the chance to hear and judge and make their own assessments.